Motherhood and Higher Education: Experiences of Student-Mothers at the University for Development Studies, Institute of Distance and Continuing Learning, Sawla Study Centre, Ghana - Rashid Osuman; Joseph Yaw Dwamena Quansah; Dacosta Aboagye (Journal of Education and Learning Technology)
Student-mothers in distance education programmes must balance traditional domestic roles with their academic pursuits. This study sought to determine the experiences of student mothers in balancing motherhood and higher education at the Institute of Distance and Continuous Learning (ICDL) of the University for Development Studies (UDS), Sawla Study Centre, Ghana. The fundamental theoretical support for this study is grounded in Role Conflict Theory. This study employed a quantitative research approach using a descriptive survey design and guided by the positivist or post-positivist paradigm. A questionnaire was used to collect data from all the 51 student mothers at the IDCL. Descriptive statistics of means and standard deviations were used to analyse the data collected. The study found that student mothers are overwhelmed with various non-academic responsibilities such as cooking, childcare, fetching water, and household chores. The study further indicated that student-mothers who juggle various non-academic activities in their daily lives, while balancing these roles with their academic pursuits, experience negative effects on both their academic performance and family life. The study concludes that student mothers face unavoidable academic obstacles from their non-academic responsibilities. Therefore, the study recommends that IDCL, in collaboration with the Counselling Unit of the university should provide intensive counselling services during freshers’ orientation programmes to make them aware of the academic challenges facing female students who conceive or give birth while pursuing their various programmes at the study centres. This study contributes to scholarship by shedding light on the unique challenges faced by student-mothers in distance education, particularly within the context of the IDCL.